Promotion Mix Strategy in Promoting a Halal Brand in Indonesia: a Case Study on Sasha Halal Toothpaste - Leva Fairus; Nurul Setiorini; Usep Abdul Matin (JURNAL INDO-ISLAMIKA, 2021)
As a country with the largest Muslim population in the world, Indonesia has a large Muslim market and growing halal industry. Now many Indonesian brands are using the halal label not only to comply with their regulations, but also to attract their consumers. One of the brands, which has made the halal label a brand, is the Sasha Halal Toothpaste. It is a brand launched by PT. Kino Indonesia, Tbk (Kino). This brand builds an image as an Islamic toothpaste that not only functions as a cleanser, but also satisfies its Muslim consumers. Kino itself is a consumer goods company from Indonesia, which was founded in 1999 by Harry Sanusi, and has become a public company in 2015. Kino launched Sasha Halal Toothpaste in 2018. In a relatively short period of time, this brand was able to generate its products, and be accepted in the toothpaste market in Indonesia. competing with competitors who have become long-standing players in this market. One of the things that drives this is Kino implementing a promotion mix strategy in promoting Sasha Halal Toothpaste. This study provides an overview of the promotion mix strategy of the Sasha Halal Toothpaste. This strategy has led people in Indonesia to be aware of this brand, including a combination of several methods such as advertising, sales promotion, interactive/digital marketing, public relations, events and experiences. This study uses a decsriptive qualitative method, and obtains its data by interviews with Ms. Danti Yulia Nastiti, a brand manager of Kino, including by online and visual data documentation.